Necessidades formativas para a docência em geografia na educação básica - Much, Liane Nair (2017)
The research reported here aimed to "establish possible relations between the training needs pointed out by Geography teachers working in Basic Education and Knowledge Needed to teach presented in the Specialized Literature". Having identified the training needs of those teachers and establishing such relationships, we understand that we will have sufficient basic elements to subsidize the organization and the implementation of formative actions, which seek, at one time, to articulate the professional development of Basic Education teachers and institutional development of the units where those teachers work. Based on the Specialized Literature we established to use in this study a teaching knowledge typology with 7 categories; each one related to a type of knowledge: disciplinary, curricular, experiential, educational sciences, pedagogical tradition, students and their characteristics, pedagogical of the subject. In order to operationalize the information’s collection, we set out to answer the following research problem: In what ways do the training needs permeate the teaching practice of Geography teachers working in Basic Education? In order to answer this question, the following research questions were elaborated: 1) What training needs are usually identified by BE Geography teachers in the development of their teaching practice? 2) What are the situations experienced by BE Geography teachers in their professional life that usually trigger their training needs? 3) How do Geography teachers of Basic Education usually seek answers to their training needs?; 4) What training actions are usually offered by BE schools to assist teachers in overcoming their training needs? For the collection of information, we have the collaboration of 14 professors licensed in geography who work in schools of the State Public School Network (SPSN / RS), located in Santa Maria. The instruments used for the collection of information were structured interview and observation of classes. All 14 teachers were interviewed and 7 of them allowed us to attend their classes. Thus, 46 classes were attended in the period from October to November 2016 and from April to May 2017. For the organization and treatment of the information collected, we use the guidelines derived from the Grounded Theory. From the analysis carried out, we could observe the following findings. 1) Those teachers feel training needs of knowing different didactic-pedagogical strategies; update themselves in curricular and pedagogical knowledge of Geography. Learn how to work with students with disabilities; know different evaluation models; learn how to use Information Technology (ICT); learn how to work on cross-cutting themes and learn learning theories, rewrite the school's Political-Pedagogical Project; and learn how to work didactically with projects. 2) These needs generally arise from perceived difficulties and situations experienced by teachers in the daily school life, such as students with no motivation, difficulties in working certain contents in class; teacher’s limitations in using computers as a pedagogical resource, students with disabilities included in the class. 3) These teachers carry out some movements in search of solutions such as: the dialogue with students to identify the refusal to the proposed work. Participate in courses and seminars to learn, update themselves; contextualization of content based on the student's reality and others acquire materials (books, magazines) for self-training, and in specific cases, it has been reported that they ask for help to the school's governing staff. 4) Among the formative actions that schools organize and offer were mentioned: meetings, lectures with varied themes, chosen by the pedagogical coordination of the school; digital literacy workshops; and there are also opportunities for dialogue so that all teachers can find answers to the problems they face. At the end, it was possible to establish the following correspondence relations between the set of training needs expressed by those teachers and the typology of teaching knowledge that we adopted as the basis of this study. All 7 categories of knowledge of this typology were contemplated, so that each expressed need could be associated with at least 2 types of teacher knowledge of this typology.